2014
DOI: 10.1371/journal.pone.0086868
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses Induced by Obstructive Apnea Are Enhanced in Hypertensive Rats Due to Enhanced Chemoreceptor Responsivity

Abstract: Spontaneously hypertensive rats (SHR), like patients with sleep apnea, have hypertension, increased sympathetic activity, and increased chemoreceptor drive. We investigated the role of carotid chemoreceptors in cardiovascular responses induced by obstructive apnea in awake SHR. A tracheal balloon and vascular cannulas were implanted, and a week later, apneas of 15 s each were induced. The effects of apnea were more pronounced in SHR than in control rats (Wistar Kyoto; WKY). Blood pressure increased by 57±3 mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In recent years, OSAS has been increasingly recognized as a risk factor for both systemic and ocular diseases. For example, past studies have demonstrated that the risks of developing diabetes, stroke, hypertension, and atherosclerosis are increased in OSAS patients [ 5 , 43 , 44 ]. In ophthalmology, besides glaucoma, papill edema, non-arteritic ischemic optic neuropathy (NAION), and other ocular disorders have also been considered as potential lesions due to intermittent nocturnal hypoxia caused by OSAS [ 4 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, OSAS has been increasingly recognized as a risk factor for both systemic and ocular diseases. For example, past studies have demonstrated that the risks of developing diabetes, stroke, hypertension, and atherosclerosis are increased in OSAS patients [ 5 , 43 , 44 ]. In ophthalmology, besides glaucoma, papill edema, non-arteritic ischemic optic neuropathy (NAION), and other ocular disorders have also been considered as potential lesions due to intermittent nocturnal hypoxia caused by OSAS [ 4 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…) or the pressor response (Angheben et al. ) to airway obstruction. Collectively, these findings indicate that activation of carotid chemoreceptor afferents partially contribute to the sympathetic and cardiorespiratory changes during airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A 15 sec balloon inflation decreases arterial O 2 saturation~20%, increases CO 2 and respiratory effort, and produces a pressor response (Schoorlemmer et al 2011). Carotid body denervation (CBD) attenuates the cardiovascular responses to airway obstruction in nonanesthetized rats (Angheben et al 2014). Furthermore, CBD did not reduce the neuronal activation evoked by obstructive apnea in ventrolateral medulla of regions involved in the respiratory and autonomic control (Ferreira et al 2015).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations